2006
DOI: 10.1097/01.cpm.0000246808.28791.3e
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Steroids for the Treatment of Acute Asthma

Abstract: Despite over 50 years of clinical experience, many uncertainties persist with respect to the onset of action, doseresponse characteristics, duration of treatment, and optimal route of administration of systemic steroids when used in the treatment of severe acute asthma. Studies show that treating severe acute asthma with systemic corticosteroids within 1 hour of presentation to the emergency department lowers hospitalization rates and improves pulmonary function. The onset of action may be seen in as little as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…A Cochrane review (six trials; 374 patients) found that the use of corticosteroids was associated with significant reduction in the number of relapses, hospitalization rates and use of SABAs. [ 348 349 ] In another review of 12 studies involving 863 patients, administration of corticosteroids within 1 h of presentation was associated with a significant reduction in hospital admission rates with a number needed to treat of eight, with no increase in adverse effects. [ 350 ] In a meta-analysis of six trials (344 adult patients) comparing the dose and route of administration of corticosteroids in hospitalized patients, it was found that low-dose systemic steroids (≤80 mg/day of methylprednisolone or ≤400 mg/day of hydrocortisone or <100 mg/day of prednisolone) were equally effective when compared to either medium-dose (>80 mg ≤360 mg/day of methylprednisolone or > 400 ≤1800 mg/day of hydrocortisone, or >100mg ≤450 mg/day of prednisolone) or high-dose (>360/day of methylprednisolone or >1800 mg/day of hydrocortisone or 450 mg/day of prednisolone) corticosteroids.…”
Section: F Management Of Acute Exacerbations Of Asthmamentioning
confidence: 99%
“…A Cochrane review (six trials; 374 patients) found that the use of corticosteroids was associated with significant reduction in the number of relapses, hospitalization rates and use of SABAs. [ 348 349 ] In another review of 12 studies involving 863 patients, administration of corticosteroids within 1 h of presentation was associated with a significant reduction in hospital admission rates with a number needed to treat of eight, with no increase in adverse effects. [ 350 ] In a meta-analysis of six trials (344 adult patients) comparing the dose and route of administration of corticosteroids in hospitalized patients, it was found that low-dose systemic steroids (≤80 mg/day of methylprednisolone or ≤400 mg/day of hydrocortisone or <100 mg/day of prednisolone) were equally effective when compared to either medium-dose (>80 mg ≤360 mg/day of methylprednisolone or > 400 ≤1800 mg/day of hydrocortisone, or >100mg ≤450 mg/day of prednisolone) or high-dose (>360/day of methylprednisolone or >1800 mg/day of hydrocortisone or 450 mg/day of prednisolone) corticosteroids.…”
Section: F Management Of Acute Exacerbations Of Asthmamentioning
confidence: 99%
“…Further bronchodilation can be achieved with combination of ipratropium with salbutamol (224)(225)(226). Systemic glucocorticosteroids should be administered orally or intravenously as they accelerate the resolution of exacerbation (0.5 mg/kg for 7-10 days) (1,34,50,(227)(228)(229).…”
Section: Management Of Exacerbationsmentioning
confidence: 99%
“…However, despite extensive clinical experience with these agents, there remains considerable uncertainty as to the onset of action, dose-response characteristics, duration of treatment, optimal route of administration and the patient population likely to require or respond to corticosteroids in emergency situations when used for the treatment of acute severe asthma. [78] The treatment of acute severe asthma with corticosteroids within 1 hour of presentation to the emergency department lowers hospitalization rates and improves pulmonary function. [79] Their onset of action may be seen in as little as 2 hours in studies measuring peak flow, but may be delayed as much as 6 hours in studies using FEV 1 as the pulmonary function outcome measure.…”
Section: Corticosteroidsmentioning
confidence: 99%